2012
DOI: 10.1093/eurheartj/ehs341
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific differences in left ventricular remodelling in obesity: insights from cardiovascular magnetic resonance imaging

Abstract: In the absence of traditional cardiovascular risk factors, obese men show predominantly concentric hypertrophy, whereas obese women exhibit both eccentric and concentric hypertrophy. As concentric hypertrophy is more strongly related to cardiovascular mortality than eccentric hypertrophy, our observations may explain the observed gender difference in obesity-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 30 publications
5
74
0
1
Order By: Relevance
“…18 The intraobserver coefficient of variation for RV mass with this method is excellent (9% RV-end-diastolic volume [EDV] and 12% RV mass in this study), and in keeping with previously reported data from this group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…18 The intraobserver coefficient of variation for RV mass with this method is excellent (9% RV-end-diastolic volume [EDV] and 12% RV mass in this study), and in keeping with previously reported data from this group.…”
Section: Discussionsupporting
confidence: 90%
“…25 Potential mechanisms for this have focused on the LV, including concentric hypertrophy, 18 diastolic dysfunction, 16 impaired myocardial energetics, 26 and increased aortic stiffness, 27 all of which are present in obesity and are independent markers of elevated cardiovascular risk. Although relatively underinvestigated, RV hypertrophy is also present in obesity 9,10 and is emerging as another risk factor for heart failure and cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased left ventricular mass index is an independent predictor for cardiovascular morbidity and mortality. 18 The average 19-g-higher left ventricular mass in young adults born preterm is equivalent to that associated with a 9-kg/m 2 increase in body mass index 19 and in longitudinal studies would equate to a >50% increased risk of cardiovascular clinical events in later adult life. 20,21 The major cardiovascular risk previously identified in those born preterm is their higher blood pressure, 9 which could have accounted for a proportion of the increased left ventricular mass.…”
Section: Discussionmentioning
confidence: 99%